Dreamed gestures: a case of architectural design communication through drawing - Magalhães, Graça Maria Alves dos Santos (2014)
Here, we aim to discuss that which generally refers to the contribution of drawing in the understanding of the design project, and particularly in relation to its communication in architecture. From a heuristic perspective, it is accepted that drawing recreates ‘ways of seeing’ which facilitate the project. Through its functions in supporting and stimulating the idea, throughout the project, drawing contributes to the idea’s development in accordance with the stratified process of design. We present a case study of project communication by considering drawings by the architect Rui Pacheco (1929 - ) which were created in response to a commission from renowned Portuguese architects in the second half of the twentieth century, in order to provide a three-dimensional prediction and to commercially communicate architectural projects among promoters. Anticipating three-dimensional modelling with digital technology, Rui Pacheco constructed images through a complex methodological process which departed from the two-dimensional representation of the project, in favour of a three-dimensional model which would serve as a blueprint for the new two-dimensional images – such as with European painting in the seventeenth century. In this case, the representation exceeds the functional consideration of the project, in that the modes involved in the drawing participated in the idealization of the heterotopic representation, steering the perception constructed by the public, users or by the designers themselves. Through this research, we aim to contribute to critical debate and to the multidisciplinary nature of drawing, design and architecture, intersecting the practice of drawing with the project, so as to encourage an understanding of the interdisciplinary potential in generating new ideas and solutions which the project seeks to address.